2017
DOI: 10.1534/g3.116.037069
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of lncRNA and mRNA Expression During Differentiation of Abdominal Preadipocytes in the Chicken

Abstract: Long noncoding RNAs (lncRNAs) regulate adipogenesis and other processes associated with metabolic tissue development and function. However, little is known about the function and profile of lncRNAs during preadipocyte differentiation in the chicken (Gallus gallus). Herein, lncRNA and mRNA expression in preadipocytes at different stages of differentiation were analyzed using RNA sequencing. A total of 1,300,074,528 clean reads and 27,023 novel lncRNAs were obtained from 12 samples. The number of genes (1336 lnc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 62 publications
6
54
0
Order By: Relevance
“…It was inferred that the 11 key lncRNAs such as XLOC_004398, XLOC_0053194, and XLOC_046142 could regulate the proliferation and differentiation of intramuscular adipocytes as well as lipogenesis in LW and LY pigs by target regulating these genes involved in p38 MAPK signaling pathway. The results were similar to those of Zhang et al, who found that the target genes of lncRNAs in abdominal fat tissue of chicken were significantly enriched in MAPK signaling pathway [18]. Note that XLOC_046142 might play a critical role in MAPK signaling pathway by trans-acting on MAPKAPK2.…”
Section: Pigssupporting
confidence: 89%
See 2 more Smart Citations
“…It was inferred that the 11 key lncRNAs such as XLOC_004398, XLOC_0053194, and XLOC_046142 could regulate the proliferation and differentiation of intramuscular adipocytes as well as lipogenesis in LW and LY pigs by target regulating these genes involved in p38 MAPK signaling pathway. The results were similar to those of Zhang et al, who found that the target genes of lncRNAs in abdominal fat tissue of chicken were significantly enriched in MAPK signaling pathway [18]. Note that XLOC_046142 might play a critical role in MAPK signaling pathway by trans-acting on MAPKAPK2.…”
Section: Pigssupporting
confidence: 89%
“…LncRNAs, nonprotein coding transcripts longer than 200 nucleotides, have important regulatory functions in adipogenesis and lipid metabolism. With the development of high throughput sequencing technology, RNA-seq has been widely applied in the identification and functional analysis of lncRNAs and mRNAs of adipose tissues in pig [7,13,16,17], chicken [18], sheep [19,20] and cattle [21]. Ramayo et al [22] identified 270 and 186 lncRNAs in the liver tissues of female pigs with high and low intramuscular fatty acid contents, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6B). Interestingly, previous studies have shown that ATF4 related to positively regulating hepatic gluconeogenesis [39]. This agrees with the increased hepatic gluconeogenesis capacity observed in IUGR pigs.…”
Section: Enrichment Analysis Of Nearest-neighbor Genes Of Differentiasupporting
confidence: 89%
“…GO enrichment revealed the functions of genes in stage-specific modules, and KEGG analysis revealed signaling pathways and metabolic networks vital for breast muscle development (Zhang et al 2017a). In the current study, the GO terms for the target lncRNA genes were related primarily to biological processes and molecular functions (Fig 4).…”
Section: Predicted and Functional Analyses Of Lncrna Target Genesmentioning
confidence: 99%